Maury had a little lamb - Oke, Janette, 1935-; Munger, Nancy ([Minneapolis, MN] : Bethany Backyard, 2001)
Shandy the lamb, rejected by his mother and the other ewes, is cared for by a young boy until he is big enough to try to rejoin the flock of sheep.
13 39
Keywords: Lambs -- Juvenile fiction; Sheep -- Fiction; Orphaned animals -- Fiction; Animals -- Infancy -- Fiction; Farm life -- Fiction